2003
DOI: 10.1016/s0023-9690(02)00505-2
|View full text |Cite
|
Sign up to set email alerts
|

Cue competition as a retrieval deficit

Abstract: Four experiments using rats as subjects investigated the claim of Williams (1996) that cue competition results from an associative acquisition deficit, rather than a performance deficit. In Experiment 1, extinction of an overshadowing stimulus following overshadowing treatment increased responding to the overshadowed stimulus, thereby replicating prior observations with new parameters. In Experiment 2, an overshadowed stimulus failed to support second-order conditioning unless the overshadowing stimulus receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…The present results might be viewed as closely related to the prevention of blocking that is achieved by the blocking CS being, in turn, overshadowed (e.g., Denniston, Savastano, Blaisdell, & Miller, 2003). Specifically, Denniston et al (2003) found that AX-O trials prior to XY-O trials prevented X from overshadowing the target CS (i.e., CS Y).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The present results might be viewed as closely related to the prevention of blocking that is achieved by the blocking CS being, in turn, overshadowed (e.g., Denniston, Savastano, Blaisdell, & Miller, 2003). Specifically, Denniston et al (2003) found that AX-O trials prior to XY-O trials prevented X from overshadowing the target CS (i.e., CS Y).…”
Section: Discussionsupporting
confidence: 50%
“…Specifically, Denniston et al (2003) found that AX-O trials prior to XY-O trials prevented X from overshadowing the target CS (i.e., CS Y). In their Experiment 4, as in the present experiments, the potential of the first-order comparator (i.e., CS X in Denniston et al's [2003] experiment and CS A in our experiments) as a down-modulator of responding to the target CS (i.e., CS Y in Denniston et al's [2003] experiment and CS X in our experiments) was impaired by the second-order comparator (i.e., CS A in Denniston et al's [2003] experiment and the context in our experiments).…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that Links 2 and 3 have robust comparator stimuli themselves, their potential to down-modulate responding supported by Link 1 is attenuated, and net responding elicited by the target CS should be increased. As is true of first-order comparator stimuli, second-order comparator stimuli can be discrete (e.g., Denniston, Savastano, Blaisdell, & Miller, 2003), or they can be contextual (e.g., Blaisdell, Bristol, Gunther, & Miller, 1998). Importantly, each stimulus other than the target cue and outcome can function both as a first-order comparator stimulus (which may be down modulated by second-order comparator stimuli) and as a second-order comparator stimulus (which may downmodulate other first-order comparator stimuli).…”
Section: Resultsmentioning
confidence: 99%
“…Such phenomena are collectively called retrospective revaluation. Increases in responding to the target cue as a result of posttraining deflation of a companion stimulus are relatively easy to obtain (e.g., Denniston, Savastano, Blaisdell, & Miller, 2003), but a few failures to obtain the effect have been reported (e.g., Holland, 1999) suggesting that this effect like most effects is parameter dependent (Shevill & Hall, 2004). In contrast, decreases in responding to a target cue as a result of posttraining inflation of a companion stimulus is rarely observed when the target cue signals a biologically significant outcome such as food or footshock (e.g., Grahame, Barnet, & Miller, 1992;Miller, Hallam, & Grahame, 1990), but can be observed if the procedure is embedded in a sensory preconditioning procedure so that the target cue does not have the opportunity to control behavior until after the inflation treatment is complete.…”
Section: Absences Of Behaviors That Might Be Expected But Were Never mentioning
confidence: 99%